Taylor bubble velocity measurements in two-phase air/water vertical flow - Dinh, T. Bui (Vietnam Journal of Mechanics, 2001)
An experimental technique for the measurement of the instantaneous rising velocity of a single Taylor bubble in two-phase air/water vertical flow is proposed. Measurements are based on the multiple successive digital images and binary image processing techniques. The instantaneous velocity of a bubble is expressed as a function separation distance between the two consecutive bubble nose tips (or the position of the center of the bubble). This experimental technique allows studying and measuring with high accuracy both types of flow: full developed and developing slug flows. The major part of this work(experimental set-up, images digitization) is carried out at Kwangju Institute of Science &Technology (KJIST) in Korea.